Synthesis and Characterisation of Mg2+ and Al3+ Co-Doped CoCr2O4 Inorganic Pigments With High Near-Infrared Reflectance - Wei, Xueling; Zou, Xiangyu; Deng, Zhifeng; Bao, Weiwei; Ai, Taotao; Zhang, Qi (Frontiers in Materials, 2022)
A new class of near-infrared reflectance pigments based on Co1-xMgxCr2-yAlyO4 (x=0-1 and y=0-2) have been synthesized via Pechini-type sol-gel method. The developed powders were characterized by thermo gravimetry and differential scanning calorimetry (TG-DSC), X-ray diffraction (XRD), UV-vis-NIR diffuse reflectance spectroscopy, and CIE 1976 L*a*b* color scales. XRD patterns displayed the characteristic peaks of the spinel structure with good crystallinity. The substitution of Mg2+ for Co2+ ions in the tetrahedral positions, and Al3+ for Cr3+ ions in the octahedral positions of CoCr2O4 not only reduce the cost but also changed the color of the pigment from green to yellow and then blue. Moreover, the synthesized pigments possess high NIR solar reflectance in the range of 780-2500 nm. The thermal and chemical stability of the pigment was also studied. These facts express the potential of pigments to be employed in cool colorants.